The Effect of Ethanol Extract of Phaleria macrocarpa Fruit Combined with Deferiprone on Peripheral Blood Counts in Iron-Overloaded Rats - Rahma, Rahma; Estuningtyas, Ari (Pharmaceutical Journal of Indonesia, 2024)
Iron overload poses health risks due to its role in reactive oxygen species (ROS) formation. We evaluated the efficacy of ethanol extract of Phaleria macrocarpa Fruit (PM) against deferiprone-induced alterations in hematological parameters in iron-overloaded rats. Six groups were studied: control, iron-overloaded (IO), deferiprone (D), PM, and two combination groups (DPM-1 and DPM-2). Hematological parameters were assessed at baseline (week-3) and post-treatment (week-8), including total white blood cell count (WBC), lymphocytes (LYM), granulocytes (GRAN), platelet count (PLT), red blood cell count (RBC), hemoglobin (Hb), mean corpuscular volume (MCV, mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC). Iron overload induced mild changes, with significant increases in MCV, alongside non-significant increasing trend in LYM and decreasing trends in other parameters. Deferiprone led to significant decreases in RBC and Hb, with non-significant increases in MCV and non-significant decreases in other parameters. PM group showed significant decreased in PLT, RBC, and Hb, and a significant increase in MCV and MCH, accompanied by non-significant increase in MCHC and non-significant decreasing trends in WBC, LYM, and GRAN. Combination treatment of ethanol extract of Phaleria macrocarpa fruit with deferiprone at usual dose (DPM-1) resulted in significant changes, including decreases in GRAN, RBC, Hb and MCHC and increasing MCV, accompanied by non-significant increase in MCH and non-significant decrease in other parameter. The magnitude of parameter changes appears smaller when the dose of deferiprone is reduced in the combination group (DPM-2) compared to the DPM-1 group. PM alone exhibited minimal effects on hematological parameters compared to deferiprone (except for PLT), indicating the need for further research to elucidate the specific cellular and molecular pathways influenced by these treatments to support the use of PM as adjunct therapy in patients with iron overload.